2018
DOI: 10.1371/journal.pone.0205900
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and effect of Trichoderma isolated from the roots of Pinus densiflora within the fairy ring of pine mushroom (Tricholoma matsutake)

Abstract: Pine mushroom (PM, Tricholoma matsutake) is an important ectomycorrhizal fungus in Asia primarily due to its value as a food delicacy. Recent studies have shown that fairy rings of PM have distinctive fungal communities, which suggests that other fungi influence the growth of PM. Trichoderma is a well-known saprotrophic fungus commonly found in pine roots within PM fairy rings; however, little is known about the diversity of Trichoderma associated with PM and how these species influence PM growth. This study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…While competition between ectomycorrhiza and other microfungi are common in soil ( Leake et al, 2003 ), several studies reported growth promotion of ectomycorrhizal fungi by microfungi isolated from soil ( Ogawa, 1976 ; Oh et al, 2018 ). For instance, Trichoderma and Oidiodendron species were exclusively isolated from the T. matsutake fruiting zone of P. densiflora forests ( Ogawa, 1977 ; Oh et al, 2018 , 2019 ), and high abundance of F. oxysporum was reported in Tuber magnatum -productive areas ( Mello et al, 2010 ). Likewise, we found that ectomycorrhizal fungi, such as Suillus were less abundant in root samples with T. matsutake than those without T. matsutake .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While competition between ectomycorrhiza and other microfungi are common in soil ( Leake et al, 2003 ), several studies reported growth promotion of ectomycorrhizal fungi by microfungi isolated from soil ( Ogawa, 1976 ; Oh et al, 2018 ). For instance, Trichoderma and Oidiodendron species were exclusively isolated from the T. matsutake fruiting zone of P. densiflora forests ( Ogawa, 1977 ; Oh et al, 2018 , 2019 ), and high abundance of F. oxysporum was reported in Tuber magnatum -productive areas ( Mello et al, 2010 ). Likewise, we found that ectomycorrhizal fungi, such as Suillus were less abundant in root samples with T. matsutake than those without T. matsutake .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we found that ectomycorrhizal fungi, such as Suillus were less abundant in root samples with T. matsutake than those without T. matsutake . Trichoderma might help survival of T. matsutake by promoting plant growth, root branching, and development ( Guzmán-Guzmán et al, 2019 ), or by inhibiting the growth of other ectomycorrhiza as reported between Trichoderma viride and Suillus bovinus in soil environment ( Mucha et al, 2008 ; Sabella et al, 2015 ; Oh et al, 2018 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of molecular approaches based on nucleotide sequences resulted in better resolution to distinguish species with a similar growth morphology [52,53,54]. Although the ITS sequence is used as the fungal barcode [33], benA and tef1α are more efficiently used for the identification of Penicillium and Trichoderma , respectively [49,50]. The use of suitable markers for a particular group seems to increase species diversity and identification accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…As for the fungal species, Ogawa and Kawai [32] reported that metabolites of Mortierella species promoted the hyphal growth of PM about twofold. Similarly, metabolites of some Trichoderma species isolated within PM fairy rings also promoted PM growth [33]. We speculated that other microfungi that promote PM mycelial growth can be found within the PM fairy rings.…”
Section: Introductionmentioning
confidence: 97%